2021
DOI: 10.1111/mec.16039
|View full text |Cite
|
Sign up to set email alerts
|

Sensory‐based quantification of male colour patterns in Trinidadian guppies reveals no support for parallel phenotypic evolution in multivariate trait space

Abstract: Parallel evolution, in which independent populations evolve along similar phenotypic trajectories, offers insights into the repeatability of adaptive evolution. Here, we revisit a classic example of parallelism, that of repeated evolution of brighter males in the Trinidadian guppy (Poecilia reticulata). In guppies, colonisation of low predation habitats is associated with emergence of ‘more colourful’ phenotypes since predator‐induced viability selection for crypsis weakens while sexual selection by female pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(60 citation statements)
references
References 127 publications
3
56
1
Order By: Relevance
“…Low diversity in upstream populations is consistent with previous studies of polymorphic microsatellite or SNP markers (Barson et al, 2009;Willing et al, 2010).and very high FST values between pairs of samples from upstream populations from different rivers, though previous studies of FST either did not provide nucleotide diversity estimates (Suk & Neff, 2009;Fraser et al, 2015) or did not detect bottlenecks (Willing et al, 2010). FST estimates using the same PoolSeq data as analysed here (Yong et al, 2021 see Supplementary Table S2), support the same pattern, and a recent population genomics study using all site types inferred the occurrence of bottlenecks in several rivers (Whiting et al, 2021). Our analyses of synonymous, probably weakly selected, variants in coding sequences reveals specific loss of rare variants, as expected if upstream populations are recovering after having lost diversity in their recent history.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Low diversity in upstream populations is consistent with previous studies of polymorphic microsatellite or SNP markers (Barson et al, 2009;Willing et al, 2010).and very high FST values between pairs of samples from upstream populations from different rivers, though previous studies of FST either did not provide nucleotide diversity estimates (Suk & Neff, 2009;Fraser et al, 2015) or did not detect bottlenecks (Willing et al, 2010). FST estimates using the same PoolSeq data as analysed here (Yong et al, 2021 see Supplementary Table S2), support the same pattern, and a recent population genomics study using all site types inferred the occurrence of bottlenecks in several rivers (Whiting et al, 2021). Our analyses of synonymous, probably weakly selected, variants in coding sequences reveals specific loss of rare variants, as expected if upstream populations are recovering after having lost diversity in their recent history.…”
Section: Discussionsupporting
confidence: 82%
“…Low coverage Illumina sequencing was done for separate male and female pools, each of 20 individuals, for each sample, yielding sequence lengths of 150 bp, and the raw sequence reads from the 24 pools were processed as described previously (Yong, Croft, Troscianko, Ramnarine, & Wilson, 2021). Briefly, reads were trimmed to remove low quality bases and adapter sequences using cutadapt .…”
Section: Methodsmentioning
confidence: 99%
“…Discerning the role of predation on colour pattern evolution requires controlling for differences among drainages. Other studies have found results that are consistent with Endler's original work, although many studies were conducted on the Marianne River drainage (Millar et al 2006;Gotanda & Hendry 2014), where both Yong et al (2021) and Valvo et al (2021) found evidence for large changes in conspicuousness. Multiple transplant studies have found that male coloration changes when predation risk is altered (Endler, 1980;Gordon et al, 2015;Gotanda et al, 2019;Kemp et al, 2018).…”
Section: Introductionsupporting
confidence: 65%
“…What are we to make of these three separate studies? Do the results of Millar and Hendry (2012), Valvo et al (2021), and Yong et al (2021) invalidate our long‐held assumptions about colour evolution in guppies? Before answering this question, five points deserve consideration.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation